ANALISIS POTENSI PEROLEHAN SUARA PARTAI GOLKAR PADA PEMILU LEGISLATIF 2014 DI KOTA SEMARANG - Anjar Isa Kusuma; Budi Setyono; Nunik Retno . (Journal of Politic and Government Studies, 2014)
This study was conducted to explain how Golkar chance to win the 2014 legislative elections in the city of Semarang, both in the scale of the vote and of seats in Parliament in Semarang. The things will be the basis of the observations is the target of the vote and seats as well as a political marketing strategy ahead of the 2014 elections Golkar in Semarang, strengths and weaknesses of the Golkar party in Semarang city today, as well as the level of community support for Golkar Semarang.This study will use a mixed methods or qualitative-quantitative where researchers will use qualitative methods to collect the data written and spoken words of research subjects and informants. In addition, researchers using quantitative2methods that manifested by the use of a questionnaire to measure the level of community support numerically.The results showed that the Golkar chair set acquisition with an estimated 8-9 vote totals for voice 80000-90000. Golkar try to focus on winning the election and local scale by using a personalized approach and promotion strategies of candidates through various media to attract the support of the community Semarang. They are quite benefited with the large popularity of competent candidates and candidate - though also have the problem of the threat and the level of materialism abstentions Semarang people. Primarily, they are optimistic to achieve the targets that they have created. However, their optimism does not correspond with the level of community support for Golkar Semarang. Because, the Semarang people are not too keen to choose Golkar due to various reasons such as more interested in choosing the other party and the notion that politics is full of corruption. Furthermore, this study only found Golkar loyalist sympathizers and minimal amounts.